1996
DOI: 10.1046/j.1365-3083.1996.d01-67.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐Cell Receptor Diversity Expressed by CD4+ T Cells Activated by Primary Allogeneic HLA‐DR Stimulation: Estimation of the Degree of CDR3 Diversity

Abstract: In order to analyse the diversity of T-cell receptors (TCRs) expressed by the T-cell population activated by allogeneic HLA-DR stimulation, TCR beta cDNA was synthesized from mRNA of human CD4+ T cells that had been stimulated in a primary mixed lymphocyte reaction (MLR). The TCR beta cDNA was amplified by the polymerase chain reaction (PCR), subjected to bacterial cloning, and sequenced from V beta through J beta. Twenty-six different V beta and 10 different J beta segments were detected among 56 randomly sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…basic in-vitro studies, Onda et al demonstrated that T cells stimulated in vitro with primary allogeneic HLA-DR antigens show as great a CDR3 diversity as those stimulated nonspecifically with anti-CD3 specific antibody [10]. In contrast, T cells stimulated with a single peptide as an antigen showed more restricted CDR3 diversity, which implies that TCRs involved in direct allo-recognition can exhibit much greater diversity compared with those involved in indirect allo-recognition [10,11]. Even when the single mismatched HLA locus (HLA-DR1) was targeted, a highly variable CDR3 or junctional sequence was shown for allo-reactive T-cell clones [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…basic in-vitro studies, Onda et al demonstrated that T cells stimulated in vitro with primary allogeneic HLA-DR antigens show as great a CDR3 diversity as those stimulated nonspecifically with anti-CD3 specific antibody [10]. In contrast, T cells stimulated with a single peptide as an antigen showed more restricted CDR3 diversity, which implies that TCRs involved in direct allo-recognition can exhibit much greater diversity compared with those involved in indirect allo-recognition [10,11]. Even when the single mismatched HLA locus (HLA-DR1) was targeted, a highly variable CDR3 or junctional sequence was shown for allo-reactive T-cell clones [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Random cDNA clone sequence analysis. Double-stranded TCRA and TCRB cDNAs were synthesized and amplified by the anchor-ligation PCR method, as described previously [10,18]. Briefly, a synthetic double-stranded anchor was added to the upstream region of the cDNA by blunt-ended ligation and the anchored cDNA was amplified by 30 PCR cycles using a primer complementary to the anchor in combination with either the TCRAC primer FPR16 or TCRBC primer FPR27.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we carried out random cDNA cloning of the TCRs utilized for allogeneic HLA-DRB1*0406 recognition by the responder cells. The TCR cDNAs prepared from the MLR-activated CD4 þ T cells of 1CF, HID and KT14 were subjected to the anchorligation PCR, in which a synthetic anchor ligated in the upstream region of the cDNA enabled PCR-amplification of TCR cDNAs with different TCRV segments to be achieved equally efficiently [10,18]. Of the 41-44 randomly selected clones, those derived from 1CF, HID and KT14 yielded 39, 40 and 39 productive TCRA cDNA clones and 40, 41 and 43 productive TCRB cDNA clones, respectively.…”
Section: Sequence Analysismentioning
confidence: 99%
See 2 more Smart Citations